Screening Wheat Genotypes for Drought Tolerance and Co-relation Study among Morpho-physiological Traits - Pokhrel, Dipendra; Baral, Kiran; Ojha, Bishnu R; Ghimirey, Surya K; Pandey, Madhav P (Journal of Agriculture and Environment, 2013)
Wheat crop in developing world including Nepal is grown under rainfed condition and thus face moisture stress at one or more growth stages limiting grain yield. An experiment was conducted at Greenhouse to screen the 60 different genotypes of wheat including Nepalese landraces, commercial cultivars CIMMYT derived advanced lines, NWRP derived advanced lines, and three international drought tolerant check cultivars. The wheat genotypes were grown in pots (single plant) arranged in a replicated split plot design under two contrasting moisture regimes, optimum and moisture stressed. The genotypes were evaluated for water use, water use efficiency, plant height, number of tillers and biomass production. The analysis revealed significant variance between environments and among the wheat genotypes for most of these traits. A wide range of variability was observed for water use, water use efficiency, days to anthesis, plant height, number of tillers and biomass yield in both moisture stressed and non stressed environments. Gautam showed superiority than Bhrikuti and Vijaya among Nepalese cultivar for drought adaptive physiological traits. Landrace NPGR 7504 showed high level of water use efficiency and other positive traits for drought adaptation.